Inclusion of Refugee Peers – Differences Between Own Preferences and Expectations of the Peer Group - Beißert, Hanna; Mulvey, Kelly Lynn (Frontiers in Psychology, 2022)
Given the high numbers of refugees from Syria entering Germany in the recent years, the social integration of refugee youth has become an increasingly important issue in Germany. Thus, the current study examines adolescents’ decisions and reasoning around the inclusion of Syrian peers in Germany. Using a hypothetical scenario, we assessed adolescents’ (N = 100, M = 13.65 years, SD = 1.93, 51 females, 49 males) peer inclusion decisions and reasoning with attention to comparing inclusion of a Syrian refugee peer and a German peer. Given the importance of group norms for adolescents, we assessed not only adolescents’ own inclusion decisions, but also what they would expect their peer group to decide and what they think their peer group should do. Moreover, adolescents’ underlying reasoning was assessed. The analyses revealed that adolescents thought they would be more inclusive of a Syrian peer than a German peer and that their peer group should be more inclusive of a Syrian peer than a German peer. These tendencies toward including refugees were justified with references to morality as well as social-conventions. In contrast to their own decisions and to what they think their peer group should, participants expected their group would be more inclusive toward a German peer than a Syrian peer. This was mainly justified by referencing aspects of group functioning and psychological information about the peers, whereas moral and prosocial reasoning was very rarely used for the expected group decision. In sum, these findings document that adolescents in Germany wish to be inclusive regarding refugee peers and that they balance attention to morality and other domains of social reasoning when thinking about inclusion decisions while they expect that their peers will not consider morally relevant information when making these decisions. These findings have important practical implications as they indicate the importance of interventions that focus on promoting inclusive peer group norms.